Hate speech and polarization in participatory society - Pérez-Escolar, Marta; Noguera-Vivo, José Manuel (Routledge, Taylor & Francis Group, 2022)
"The book brings together an international team of experts, enabling a broad, multidisciplinary approach that examines hate speech, dislike, polarization, and enclave deliberation as cross axes that influence offline and digital conversations. The diverse case studies herein offer insights into international news media, television drama and social media in a range of contexts, suggesting an academic frame of reference for examining this emerging phenomenon within the field of communication studies. Offering thoughtful and much-needed analysis, this collection will be of great interest to scholars and students working in communication studies, media studies, journalism, sociology, political science, political communication, and cultural industries"--
Keywords: Hassrede; Communication / Social aspects; Hate speech; Mass media / Political aspects; Polarization (Social sciences); Essays